Clinical efficiency and dermoprotection of 2-ethyl-6-methyl-3-hydroxypyridine succinate drug in case of psoriasis: from the antioxidation point of view - V. A. Visir; G. I. Makurina (Zaporožskij Medicinskij Žurnal)
Objective. To study the clinical significance of oxidative processes modulation within frames of 2-ethyl-6-methyl-3-hydroxypyridine succinate dermatropic efficiency assessment in patients with psoriasis affected by arterial hypertension.